DOPAMINERGIC GENOTYPE AND RESILIENCE TO SMALL VESSEL DISEASE ASSOCIATIONS WITH SLOWER GAIT SPEED. (11th November 2018) - Rosso, A L; I Bohnen, N; J Launer, L; J Aizenstein, H; Yaffe, K; Rosano, C
Abstract: We assessed associations of slow gait with measures of dopaminergic (catechol-O-methyltransferase (COMT) genotype, indicator of synaptic dopamine levels) and vascular (white matter hyperintensities (WMH), dichotomized at the median) factors in a cohort of older adults (n=215; age= 82.6 (SD=2.6); 58.0% female; 38.8% black; 35 Met/Met COMT Val158Met (higher dopamine) genotype). Mean gait speed was 0.92 m/s. There was a significant interaction (p=0.048) between WMH and COMT. Stratified analyses reveled a strong association between WMH and gait speed among COMT Val carriers (beta=-9.9, CI: -16.5, -3.3; lower dopamine), but not for Met/Met (beta=5.3, CI: -14.4, 24.9; higher dopamine) independent of covariates. Differences persisted over four years of follow-up. Higher synaptic dopamine, as indicated by COMT genotype, may have a protective effect on gait speed in the presence of WMH. The dopaminergic system may be an intervention target for increasing brain resilience and enhancing functional outcomes in older adults.